Long-Term Denervated Rat Schwann Cells Retain Their Capacity to Proliferate and to Myelinate Axons in vitro - Gordon, Tessa; Wood, Patrick; Sulaiman, Olawale A. R. (Frontiers in Cellular Neuroscience, 2019)
Functional recovery is poor after peripheral nerve injury and delayed surgical repair or when nerves must regenerate over long distances to reinnervate distant targets. A reduced capacity of Schwann cells (SCs) in chronically denervated distal nerve stumps to support and interact with regenerating axons may account for the poor outcome. In an in vitro system, we examined the capacity of adult, long-term denervated rat SCs to proliferate and to myelinate neurites in co-cultures with fetal dorsal root ganglion (DRG) neurons. Non-neuronal cells were counted immediately after their isolation from the distal sciatic nerve stumps that were subjected to acute denervation of 7 days or chronic denervation of either 7 weeks or 17 months. Thereafter, equal numbers of the non-neural cells were co-cultured with purified dissociated DRG neurons for 5 days. The co-cultures were then treated with 3H-Thymidine for 24 hours to quantitate SC proliferation with S100 immunostaining and autoradiography. After a 24 day period of co-culture, Sudan Black staining was used to visualize and count myelin segments that were elaborated around DRG neurites by the SCs. Isolated non-neural cells from 7 week chronically denervated nerve stumps increased 2.5-fold in number compared to ~2 million in 7 day acutely denervated stumps. There were only <0.2 million cells in the 17 week chronically denervated stumps. Nonetheless, these chronically denervated SCs maintained their proliferative capacity although the capacity was reduced to 30% in the 17 month chronically denervated distal nerve stumps. Moreover, the chronically denervated SCs retained their capacity to myelinate DRG neurites: there was extensive myelination of the neurites by the acutely and chronically denervated SCs after 24 days co-culture. There were no significant differences in the extent of myelination. We conclude that the low numbers of surviving SCs in chronically denervated distal nerve stumps retain their ability to respond to axonal signals to divide and to elaborate myelin. However, their low numbers consequent to their poor survival and their reduced capacity to proliferate account, at least in part, for the poor functional recovery after delayed surgical repair of injured nerve and/or the repair of injured nerves far from their target organs.